Kitab al-Qiraa’ah al-Rasyiidah al-Juz al-Awwal: Tahliil al-Qiyam al-Diiniyyat fi Nazhariyyat al-Imaam al-Ghazaalii wa ‘Alaaqatuhaa bi Ta’liim Mahaarah al-Qira’ah: كتاب القراءة الرشيدة الجزء الأول: تحليل القيم الدينية في نظرية الإمام الغزالي وعلاقتها بتعليم مهارة القراءة - Bahjatul Waafiroh; Mukaromah, Muhimmatul; Mohamed Rady Mohamed Elpaz Elsheakh (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
Abstract This study aims to identify the religious values embedded in the book "al-Qira'ah al-Rasyidah" and analyze it from the perspective of Imam al-Ghazali, and examine their correlation with reading skill acquisition. This research employs a qualitative method with content analysis on the first part of the book "al-Qira'ah al-Rasyidah". Data collection involved a thorough analysis of the text, identifying keywords, phrases, and themes related to religious values. These identified values were then compared and contrasted with the philosophical and pedagogical perspectives of Imam al-Ghazali to gain a deeper understanding of their significance. The findings reveal that the book is rich in religious values such as responsibility, sincerity, cooperation, honesty, and patience. These values not only support the development of reading skills but also contribute to the formation of a well-rounded student character. The study highlights a significant congruence between the values in the book and Imam al-Ghazali's perspective on character education. Both the book and Imam al-Ghazali emphasize the importance of integrating religious values into the learning process, recognizing that education should not only focus on intellectual development but also moral and spiritual growth. By analyzing the "al-Qira'ah al-Rasyidah" book through the lens of Imam al-Ghazali's thought, this study sheds light on the potential of Islamic educational texts to promote character development and foster a sense of responsibility and empathy among students. ملخص يهدف هذا البحث إلى تحديد القيم الدينية المضمنة في كتاب "القراءة الرشيدة" وتحليلها في نظرية الإمام الغزالي، ومعرفة علاقتها بتعليم مهارة القراءة. يستخدم هذا البحث المدخل النوعي. وأما منهجه فيستخدم البحث المكتبي بتحليل المحتوى للجزء الأول من كتاب "القراءة الرشيدة". تضمن جمع البيانات تحليلًا شاملاً للنص، وتحديد الكلمات الرئيسية والعبارات والموضوعات المتعلقة بالقيم الدينية. ثم تمت مقارنة هذه القيم المحددة ومقارنتها بالمنظورات الفلسفية والتربوية للإمام الغزالي للحصول على فهم أعمق لأهميتها. تكشف النتائج أن الكتاب غني بالقيم الدينية مثل المسؤولية والإخلاص والتعاون والصدق والصبر. ولا تدعم هذه القيم تنمية مهارات القراءة فحسب، بل تساهم أيضًا في تكوين شخصية الطالب المتكاملة. وتسلط الدراسة الضوء على التطابق الكبير بين القيم الواردة في الكتاب ووجهة نظر الإمام الغزالي في تعليم الشخصية. حيث يؤكد كل من الكتاب على أهمية دمج القيم الدينية في عملية التعلم، مع الاعتراف بأن التعليم لا ينبغي أن يركز فقط على التنمية الفكرية ولكن أيضًا على النمو الأخلاقي والروحي. ومن خلال تحليل كتاب "القراءة الرشيدة" من خلال نظرية الإمام الغزالي، يسلط هذا البحث الضوء على إمكانات النصوص التعليمية الإسلامية في تعزيز تنمية الشخصية وتعزيز الشعور بالمسؤولية والتعاطف بين الطلاب.